Postoperative ileus after emergency surgery for acute bowel obstruction : a case-control study of predictors and impact on recovery - Amati, Anca-Laura; Kümmel, Niklas; Negruta, Nicoleta; Reichert, Martin; Schwandner, Thilo; Noll, Julia; Braun, Jaqueline; Grau, Veronika; Petzoldt, Sebastian; Hecker, Andreas; Justus Liebig University Giessen (My University, 2025)
Purpose: Acute bowel obstruction (ABO) is a common indication for emergency abdominal surgery, often performed on a severely dilated intestine with compromised barrier function. The recovery of bowel motility in this acute setting differs from elective surgery and remains insufficiently investigated. Yet, its understanding is crucial for improving perioperative care in surgical emergencies. This study aimed to identify risk factors for postoperative ileus (POI) after emergency surgery for ABO and to explore its impact on postoperative outcomes. Methods: We retrospectively analyzed 466 patients who underwent emergency surgery for ABO between 2014 and 2020, of whom 156 developed POI. POI was defined as the absence of postoperative bowel movement requiring intravenous prokinetic therapy following an insufficient response to initial conservative measures, including oral laxatives. Perioperative predictors for POI were identified by univariate and multivariate logistic regression. The association between POI and adverse postoperative outcomes was examined using correlation analysis. Results: Multivariate analysis revealed male sex (p = 0.0009), chronic steroid therapy (p = 0.0064), high postoperative SOFA score (p = 0.0037), and elevated CRP levels on postoperative day two (p = 0.048) as independent predictors for POI. Patients with POI had significantly higher rates of postoperative respiratory (p < 0.0001) and surgical complications (p = 0.0014). Conclusion: Our findings suggest sex-dependent differences and an involvement of inflammatory processes in bowel function recovery following emergency surgery for ABO. POI in this setting is associated with increased risk of postoperative respiratory complications and surgical morbidity. These results highlight the need for targeted preventive strategies and form a solid foundation for future prospective studies aimed at optimizing perioperative care and reducing POI-related morbidity in surgical emergencies.
Keywords: ddc:610